(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Three species of the genus Cervidellus, all collected in the south-western part of North America are described, i.e. C. cervus, C. doorsselaeri and C. capraeolus. The material of C. cervus agrees in most respects with the original description, although the females are shorter and the males are on average longer than the type specimens; however, the unique structure of the labial probolae is a strong indication of the conspecifi city of the two populations. The specimens of C. doorsselaeri agree well with the original description, but differ from the type population by a longer body, larger c-ratio; smaller c’-ratio; and a more posterior position of excretory pore, nerve ring and deirid in percentage of pharynx length. The specimens of C. capraeolus agree well with the original description, but differ from the type material by a more posterior position of excretory pore, nerve ring and deirid in percentage of neck length; another character separating the specimens of the two populations is the presence of tines on the inside of the primary branches of labial probolae in the Californian specimens.